2020
DOI: 10.1108/joepp-01-2020-0007
|View full text |Cite
|
Sign up to set email alerts
|

Exploring career choices of Emirati women in the technology sector

Abstract: PurposeThe study aims to explore the factors that influence Emirati women's career choice in the UAE. This study contributes to the influence of context in career choices by investigating how Emirati women chose information technology (IT) as a profession through the lens of the social cognitive career theory.Design/methodology/approachThis study undertook in-depth interviews with 21 Emirati women working in technology in the UAE. The study considers women's career choices at three levels, i.e. from an individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 63 publications
(97 reference statements)
0
15
0
Order By: Relevance
“…In [37], fathers in the UAE used the prospect of employment with prestigious government and private businesses to persuade their daughters that engineering or other STEM disciplines are logical career paths. Some of the Emirati participants reported that their mothers also wanted to see them become financially independent [36].…”
Section: Patriarchy and Male Dominancementioning
confidence: 99%
See 3 more Smart Citations
“…In [37], fathers in the UAE used the prospect of employment with prestigious government and private businesses to persuade their daughters that engineering or other STEM disciplines are logical career paths. Some of the Emirati participants reported that their mothers also wanted to see them become financially independent [36].…”
Section: Patriarchy and Male Dominancementioning
confidence: 99%
“…Some of the Emirati participants reported that their mothers also wanted to see them become financially independent [36]. As one participant noted, her mother, a homemaker, wanted her to have a degree, as her mother called that her "weapon" [37].…”
Section: Patriarchy and Male Dominancementioning
confidence: 99%
See 2 more Smart Citations
“…Women are still ascribed roles as mother and homemaker (Goby and Erogul, 2011; Tlaiss, 2013) making female employment outside the home still unusual (Itani et al, 2011). Consequently, the independent economic activity of women challenges social expectations and can invoke unfavourable attitudes towards them (Zeidan and Bahrami, 2011); thus, the career decisions of women will often be the result of careful negotiations with family (Howe-Walsh et al, 2020). Fathers in particular appear to have a strong influence on female career choices and Emirati women are often required to enter into a ‘patriarchal bargain’ to allow them to enter the workplace (Williams et al, 2013).…”
Section: Contextmentioning
confidence: 99%